Sustaining Indonesian Roots: A Tale of Families, Workers, and Students in Japan - Franggaratz, Abubakar Pae Flady Feliyenco (Universitas Negeri Surabaya, 2024)
Inspired by the tradition of “merantau,” or migration, Indonesians move globally for better opportunities while staying deeply connected to their cultural roots. In Japan, they actively preserve their culture by organizing festivals, simultaneously serving as cultural ambassadors to build connections with Japanese and international communities. To capture this journey, we conducted interviews with Indonesian families, workers, and students actively involved in organizing and participating in cultural events. The study unveils compelling stories reflecting the challenges and resilience of Indonesian migrants in Japan. A devoted mother, with her three children, drives 366 kilometers from Tokyo to Nagoya, actively participating in traditional dance practices, emphasizing the importance of cultural activities for her children’s connection to Indonesian heritage. A worker, balancing long hours in Japan while also volunteering for the Indonesian Festival, showcases the challenges of event coordination, sleeping on-site to ensure that everything is ready on the day. University students juggle their academic pressures and part-time jobs while teaching traditional dance to children, preparing them for performances and accompanying them to the stage to ease their nerves. These stories emphasize the multifaceted challenges faced by Indonesian families, workers, and students in Japan, showcasing their commitment to preserving cultural identity. Importantly, the narratives underscore the need for deeper support from the Indonesian government through funding and other means to ensure the sustainability of these efforts, reflecting the aspirations and hopes of these individuals.